Pengaruh Penurunan Tarif Pajak, Kesadaran Wajib Pajak Dan Modernisasi Sistem Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM Kota Metro - Herawati, Nurlina; Hendri, Nedi; Darmayanti, Elmira Febri (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of the reduction of taxpayers, taxpayer awareness and modernization of the tax administration system on tax compliance. The type of research used is quantitative. The sample used in this study were 97 MSME taxpayers in the city of Metro. The data analysis technique used is multiple linear regression. The results showed that the reduction in tax rates had a significant effect on MSME taxpayer compliance at KPP Pratama Metro. Taxpayer awareness affects MSME taxpayer compliance at KPP Pratama Metro. Modernization of the Tax Administration System has an effect on MSME taxpayer compliance at KPP Pratama Metro